(untitled) (Bangladesh Journal of Medical Science, 2022)
Goal: The goal of the study was to measure the public awareness on Hepatitis C (HCV) infection, in Prishtina, Kosovo’s capital. The cross-sectional survey was undertaken in October 2019 using an investigator-developed questionnaire about Hepatitis C virus knowledge. With a 95 percent confidence level and a confidence interval of 4.4, a sample size of 502 persons was calculated. Results: In terms of public awareness about the cause of Hepatitis C, 53 percent of survey participants were appropriately informed. Moreover, 54 percent of survey participants were properly informed about the transmission of Hepatitis C virus through tattooing and piercing procedures. Around 53.6 percent of survey participants were correctly informed that there is still no vaccine for protection against Hepatitis C virus. Regarding, application of knowledge in prevention, only 35.3 percent of the study participants claimed to have been tested for Hepatitis C virus during their routine blood tests. Furthermore, there exist relationship between the age group of the respondents and the knowledge regarding the question that Hepatitis C can be transmitted from the partner. The same relationship exists between the age group of the respondents and the knowledge that Hepatitis C can also be transmitted by blood transfusion and syringe exchange. Yet, other relations exist between the age group of the respondents and the knowledge regarding the chronic carrierof Hepatitis C virus but as well that pregnant women with Hepatitis C can transmit the disease to infants. Conclusion: Knowledge gaps necessitate public awareness initiatives which may increase testing and diagnosis. Knowledge on Hepatitis C virus might serve as an effective tool in decision making regarding appropriate preventive measures. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 751-758